THE LEGAL RELEVANCE OF THE METROPOLITAN REGION IN THE COOPERATIVE FEDERAL PROCESS AND ITS INFLUENCE ON MUNICIPAL ELECTIONS - Saker Neto, Demetrio; Bruno da Silva, Alexandre Antônio (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2024)
The article addresses the legal relevance of creating metropolitan regions as a means of cooperation among municipalities, states, and society in Brazil. According to the 1988 Federal Constitution, states have the power to establish metropolitan regions, urban agglomerations, and microrregions through complementary legislation, with the aim of integrating the organization, planning, and execution of public functions of common interest.This model is presented as an alternative to promoting regional development through interinstitutional cooperation and joint actions managed by the state. This allows for economic development without compromising the autonomy of municipalities, preserving their influence in municipal elections.The participation of voters in municipal elections is highlighted as an important mechanism for metropolitan regions, as it allows citizens to choose their representatives and decide on issues that directly affect their lives and those of neighboring municipalities, especially regarding public services.The article proposes conducting bibliographic and empirical research to explore this topic. Ultimately, the importance of metropolitan regions is emphasized in strengthening the federal cooperation process and reducing existing disparities in the Brazilian federation. The article seeks to reflect on the role of these regions as a means of promoting territorial cohesion and balanced development in the country. Keywords: Metropolitan Region; Federalism; Municipal Elections.